(untitled) (Fiep Bulletin - online, 2011)
The article stated below, represents the final phase of the research entitled "The Physical Education class, an inquiry from the imagination of Student Teaching in Physical Education from the “Universidad Autónoma” of Chile, Talca under the Masters Program in Human Motricity of the same University. The investigation began in September 2007 and ended in August 2008. Consequently, the article which is presented represents primarily, the background context and reference to realize the dimensions of power in which the study is based, namely, matters relating to teacher education and conception of the social imaginary, and then present the methodological design, for the interpretive paradigm, and consequently the approach from the qualitative methodology, which leads to the first data analysis with the support of software Atlas.ti. Finally, we present the conclusions that we hope will allow us to reflect on the meaning of matrices through which young people construct (s) reality (is), and therefore understand the experiences, desires and projects shared by students in training on physical education in school.